The information : a history, a theory, a flood - Gleick, James (New York : Pantheon Books, 2011)
From the invention of scripts and alphabets to the long misunderstood'talking drums' of Africa, James Gleick tells the story of information technologies that changed the very nature of human consciousness. He also provides portraits of the key figures contributing to the inexorable development of our modern understanding of information, including Charles Babbage, Ada Byron, Samuel Morse, Alan Turing, and Claude Shannon.
Includes bibliographical references (p. 429-503) and index.
Keywords: Information science -- History; Information society